ANALISIS PERMINTAAN PENUMPANG KERETA API YANG MENGHUBUNGKAN ANTAR BANDARA DITINJAU DARI COMPETITOR MARKET (Studi Kasus : Bandara Adisutjipto Yogyakarta - Bandara Adi Soemarmo Surakarta) - , SURYO PRATOMO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
A discourse about the development of multi-airport between Adisutjipto Yogyakarta Airport and Adi Soemarmo Surakarta Airport needs to be supported by providing mass transit such as train. In financial aspect, the provision of train linking two airports is more efficient because most of areas have been connected by railway network of commuter train. Therefore, a study needs to be carried out to predict the demand for the inter-airport train. However, firstly, service quality required has to be analysed. In this research, the quality of train services influencing the willingness of airline passengers using the inter-airport train is analysed by using factor analysis. Afterwards, the data obtained is processed by using stated preference techniques and ordered probit models in order to know the probabilities of the user's willingness to use train operated along the planned route. The scenario of the service model of the inter-airport train proposed in the survey consists of the estimated fare, travel time, guaranteed seating, ticket integration, and integrated schedule between trains and airplanes. Then, the results of the calculation of probabilities are multiplied with the potential users to calculate the demand of rail passangers. The results shows that the service factors required by user of the inter-airport train consists of the factor of technical performance, quality of service and travel fares. The probability of the user's willingness using the inter-airport train with the express pattern operation is 48.71%, while the probabilities of the user's willingness using the inter-airport train with the transit pattern operation (stopped at Klaten Station and Purwosari Station) is 65.36% and 53.34% for users at around the airports and the stations respectively. The calculation of the demand for the inter-airport train when it starts to be operated in 2013 is 8.574 people per day.